Endothelial TRIM35‐Regulated MMP10 Release Exacerbates Calcification of Vascular Grafts - Yiming Leng; Wei Wang; Jun Lu; Jingyuan Chen; Xuliang Chen; Yalan Li; Jie Wang; Yuanyuan Liu; Qian Tan; Wenjing Yang; Youxiang Jiang; Peiyuan Huang; et al. (Advanced Science)
Abstract Vascular calcification is a highly regulated process in cardiovascular disease (CVD) and is strongly correlated with morbidity and mortality, especially in the adverse stage of vascular remodeling after coronary artery bypass graft surgery (CABG). However, the pathogenesis of vascular graft calcification, particularly the role of endothelial‐smooth muscle cell interaction, is still unclear. To test how ECs interact with SMCs in artery grafts, single‐cell analysis of wild‐type mice is first performed using an arterial isograft mouse model and found robust cytokine‐mediated signaling pathway activation and SMC proliferation, together with upregulated endothelial tripartite motif 35 (TRIM35) expression. Unexpectedly, severe SMC calcification in artery grafts is found in TRIM35 conditional endothelial knockout (cKO) mice. Calcified medium (comprising calcium chloride and beta‐glycerophosphate)‐induced calcium deposition in vitro is also found in SMCs cocultured with TRIM35 knockout endothelium. This extraordinary phenomenon is further confirmed to be induced by increased MMP10 secretion. Mechanistically, endothelial TRIM35 inhibits MMP10 expression and secretion by promoting K63‐linked ubiquitination of RelB and maintaining its nuclear localization, consequently inhibiting nuclear transcription of MMP10 through the noncanonical NF‐κB signaling pathway. Targeting MMP10 in situ in arterial isografts can effectively alleviate vascular calcification caused by conditional endothelial TRIM35 knockout. These findings demonstrated that TRIM35 inhibited vascular calcification during arterial isograft remodeling, a process that is driven by the aberrant secretion of endothelial MMP10. Targeting MMP10 pathway may be a potential therapeutic strategy for vascular calcification in vessel grafts.